A model Ecological and Genetic Control over Thymol Biosynthesis in Essential oil Thymus L. (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
The environment at limiting factors in the Southern coast of the Crimea determine intensity of thymol biosynthesis in essential oil of Thymus vulgaris L., Th. pulegioides L. and Th. striatus Vahl. other during period. The model of ecological and genetic control thymol biosynthesis in essential oil Thymus L. is appied to the basic ontogeny phases.
Keywords: Thymus vulgaris L., Th. pulegioides L., Th. striatus Vahl., essential oil, biosynthesis of thymol, environmental limiting factors, model of ecological and genetic control.